Analysis of adipogenesis related genes and intramuscular fat composition in Angus x Nelore cattle of different gender status - Silveira, Lenise Freitas Mueller da (2021)
Cattle growth, muscle adipose tissue and fatty acid composition in different muscles, are significantly affected by gender and influenced by a variety of hormonal factors, affecting the quality of the carcass and the beef. As the adipogenesis is a complex biological process to regulate fat cell metabolism, it can be regulated by hormones and influenced by factors such as different fat deposits, the gender status and diet of cattle. Therefore, it is important to understand the molecular mechanisms involved in adipogenesis in different muscles and gender, since the deposition of fat in these animals is different, to employ new tools to add greater value to meat production. However, the present study evaluated the association of fatty acid (FA) composition and adipogenesis-related genes in the longissimus (LO) and triceps brachii (TB) muscles of feedlot Angus x Nelore cattle. A total of 150 cattle was confined for 150 days and assigned to three genders, namely, heifers, bulls, and steers, and fed the same diet. Immediately after slaughter, samples of LO and TB muscles were collected for RNA and protein extraction. Twenty-four hours after slaughter, were measured the fat thickness and marbling score between the 12th and 13th ribs and collected samples of the muscles for analyses of total lipids determination and fatty acid composition. The experimental design was completely randomized, with 50 repetitions per treatment, and each animal was considered an experimental unit. The statistical analyses were performed by the proc MIXED SAS® (version 9.3) for the meat quality traits and JMP14 Software (SAS Institute) for the gene expression analyses. There was difference in the carcass traits related to fat deposition (P ≤ 0.05). The fat thickness and marbling score were higher in heifer carcasses than in carcasses of bulls and steers. Similarly, only gender status affected the content of total lipids (P ≤ 0.05), where meat from heifers presented increased values compared to steers and bulls. There was a difference in the total saturated FAs (SFAs) by gender and muscle type (P ≤ 0.05). The meat from bulls had higher levels of SFAs compared to heifers and had no differences in relation to meat from steers. Among muscle types, total SFAs increased in LO muscle compared with TB, independent of gender. The FAs 14:0 and 16:0 were affected by muscle type only, and higher levels were detected in the LO muscle (P ≤ 0.05). There were differences in gender for total monounsaturated FAs (MUFAs; P ≤ 0.05). Meat from bulls had lower levels of MUFAs compared with the other genders. The levels of the major FA of total MUFAs, 18:1 n-9c, were higher in the LO muscle than in the TB muscle, independent of gender (P ≤ 0.05). The total polyunsaturated FAs (PUFAs), total n-3, total n-6, PUFA:SFA ratio, health index and FAs 18:2 n-6c, 20:3 n-3, and 22:4 n-6 were higher in TB than in LO muscle (P < 0.05). Otherwise, the atherogenicity and thrombogenicity indexes were higher in the LO muscle (P ≤ 0.05). Regarding the transcript levels, there was an effect of muscle type on the expression of the CEBPa and LPL (P ≤ 0.05) genes, both of which had higher expression in TB muscle. Gender affected the transcript level of ACC (P ≤ 0.05). This gene was increased in bulls, intermediate in steers, and decreased in heifers. Additionally, gender and muscle type interactions were observed for the transcript levels of FABP3, TPM2, and TPM3 (P ≤ 0.05). There was difference for tropomyosin (TPM) protein abundance between muscles only in bulls (P ≤ 0.05), where the greater TPM abundance was in the TB. Additionally, cattle gender status affected the TPM abundance evaluated in LO and TB muscles (P ≤ 0.05). The LO muscle of steers showed higher TPM abundance than bulls and heifers, while the TB muscle of bulls showed higher TPM abundance than the other genders. The cattle gender status modulated the transcripts levels of ACC gene, content of total lipids, total SFAs, total MUFAs, and carcass traits, while the muscle type affected the transcripts of CEBPa and LPL genes, total SFAs, total PUFAs, total n-3 and n-6, besides important FAs, showing a gender and muscle specific effect. In addition, a modulation of TPM in formation and accumulation of lipids was observed, related to the greater subcutaneous fat thickness and marbling score in heifers and steers, and a modulation of this same protein in muscle development, indicated by the lower fat deposition in the carcass of bulls. Furthermore, there is a different lipid profile within each muscle, where the TB muscle is more favorable to human health than the LO, and beef from heifers stands out than the other genders for presenting better carcass traits and FA composition more favorable to human health.